ex 7 b, c va rog
b )(-1)^99+[(-4)^2 ..
Anexe:
Răspunsuri la întrebare
Răspuns de
0
b) (-1)^99+[(-4)^2-2x(-3)^2]^2=-1+(16-2x9)^2=-1+(16-18)^2=-1+(-2)^2=-1+4=3
c) 0,(5):[(-3)^9:(-3)^5x(-3)^-3]^-2=0,(5):[(-3)^9-5-3]^-2=0,(5): (-3)^-2= 0,(5):9=0,06
c) 0,(5):[(-3)^9:(-3)^5x(-3)^-3]^-2=0,(5):[(-3)^9-5-3]^-2=0,(5): (-3)^-2= 0,(5):9=0,06
Alte întrebări interesante
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă